Anion Receptors for the Discrimination of ATP and ADP in Biological Media. Issue 1 (15th October 2020) - Butler, Stephen J.; Jolliffe, Katrina A.
Abstract: The design and synthesis of molecular receptors for the selective binding of nucleoside phosphate anions (e. g. ATP, ADP, GTP, GDP, UDP) in aqueous media at physiological pH is a valuable research endeavour, which could lead to new sensing tools for biomedical and drug discovery research. However, this target is very challenging due to similarities in anion size, structure and charge. This Minireview provides an account of the development of receptors capable of discriminating between ATP and ADP, and their utilisation in biological sensing applications. Particular focus is given to the application of receptors for the determination of ATP or ADP concentrations in biological media, tracking ATP levels (or the ATP/ADP ratio) in cells using fluorescence microscopy, or real‐time monitoring of enzyme reactions involving ATP and ADP in vitro . Abstract : Bind and signal : This Minireview describes progress in the development of molecular receptors that can bind and discriminate between ATP and ADP. Particular focus is given to the application of receptors for quantifying ATP or ADP levels in biological media, tracking ATP levels (or the ATP/ADP ratio) in cells using fluorescence microscopy, or real‐time monitoring of enzyme reactions involving ATP and ADP in vitro .